A política pública de recursos hídricos no Pará e a participação das populações tradicionais do Tapajós na gestão das águas e dos recursos pesqueiros - AMARAL, Lucilene Oliveira da Silva (Universidade Federal do Oeste do Pará, 2023)
In the Amazon, access to and use of water resources are essential for artisanal fishing activity and the reproduction of the riverine people's way of life. Artisanal fishermen establish, through fishing agreements, their own rules for access, use of aquatic environments and exploitation of fishing resources. However, in the state of Pará, issues related to the management of water resources are not discussed within the scope of the State Policy on Water Resources. This research aims to analyze the participation of artisanal fishermen from the Tapajós river basin in the implementation of the Water Resources Policy in Pará and its implications for the construction of public policies in the State. Quali-quantitative research is supported by methodological instruments of document analysis and bibliographic review using the official websites of the federal and state government as a database, for the analysis of legislation and technical documents on the Water Resources Policy, and the Web of Science database provided by Periodical CAPES for reviewing the scientific literature. The participation of traditional populations in spaces for discussion and implementation of public policies is analyzed from the ethnographic observation of the mobilization and articulation of artisanal fishermen in the Lower and Middle Tapajós region during the years 2020 to 2022 that resulted in the approval and implementation of the fishing on the Tapajós River in the corresponding stretch between the Tapajós-Arapiuns Extractive Reserve and the Tapajós National Forest. The results show that the State of Pará follows the systemic model of participatory management of the National Water Resources Policy, advancing slowly in the implementation of management instruments, such as basin committees, and with the management body acting centralized in the regions close to the capital of Pará. State. On the other hand, artisanal fishermen from the Lower and Middle Tapajós are organized and articulated with NGOs, universities, and other municipal, state and federal public institutions, to discuss and standardize the management of water territories through fisheries agreements. Artisanal fishermen played a key role in the creation of the rules of the fishing agreement of the RESEX Tapajós-Arapiuns and FLONA Tapajós and in the monitoring of fishing and aquatic biodiversity, inaugurating a new environment of participatory governance of water resources in Pará.